STUDI ANALISIS PERKEMBANGAN KEPRIBADIAN SIKAP PESERTA DIDIK PADA BUKU AJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS VII DI SMP PGRI KUWU KEC. KRADENAN KAB. BLORA - Ulkhotimatul Aini, Luk-luk; Nurkayati, Siti; Syaifulloh, Ahmad (Jurnal Studi Islam dan Sosial, 2022)
The background of this research is a fact that has occurred in the world of education, there are still many cases of material descriptions in Islamic Religious Education and Morals Education textbooks that are not in accordance with the level of development of students. And in middle school age coincides with adolescence. Adolescence is a period that attracts a lot of attention because of its distinctive characteristics and its decisive role in the lives of individuals in adult society. The purpose of this study was to analyze the suitability of the personality development of students' attitudes in the Islamic Religious Education and Morals Education textbook and to analyze the lack of content of the VII grade Islamic Religious Education and Morals Education textbook at SMP PGRI Kuwu. In the research that will be carried out this method uses (Library Research) library research. And this type of research is (Field Research) field research is one of the studies carried out by researchers to collect data originating from backgrounds, social interactions, individuals, groups, communities, and so on. The data collection techniques used by the author are observation, interviews, and documentation From the results of the analysis of research conducted by researchers, the personality development of students' attitudes in the seventh grade Islamic Religious Education and Morals Education textbook at SMP PGRI Kuwu is appropriate, and the shortcomings include; on the theme of Al-Qur'an Hadith does not contain material about the law of reading nun sukun/tanwin and mim sukun/tanwin, then on the theme of Fiqh it does not contain various kinds of water because they do not really understand what water is used for purification. , then on the theme of Akidah Akhlak, the presentation of material about alAsmau'u al-Husna is still a little, only explaining four names, and on the theme of History of Islamic Culture does not contain material about the names of the wives and children of the Prophet Muhammad.